Isolated microhematuria and proteinuria in adults - Seiringer, Eva (Henry Stewart Talks, 2016)
Signs of disease of the kidney or urinary tract, Evaluation and detection of microscopic hematuria, Glomerular & nonglomerular microhematuria, Transient hematuria, Detection of proteinuria, Quantification and evaluation of patients for proteinuria, Transient, orthostatic & persistent proteinuria